HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN KECEMASAN MAHASISWA TINGKAT AKHIR DALAM MENYUSUN SKRIPSI PADA MASA PANDEMI - Misalia, Roza; Zukhra, Ririn Muthia; Nauli, Fathra Annis (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022, 2022)
Covid-19 pandemic cause difficult for final year students to complete their thesis. These difficulties lead to mental problems like anxiety. One of the factors that influence anxiety is peer social support. The purpose of this study was to determine relationship between peer social support and anxiety among final year students in completing their thesis during the pandemic at Riau University.The research design used was descriptive correlational with cross sectional approach. Among 369 final students were selected by using consecutive sampling technique. The measuring instrument was used Depression Anxiety Stress Scale and peer social support questionnaire with the results of validity test using the item-total correlation, results of the value validity r > 0,444 and declared valid. Test reliability obtained the results of the value of Cronbach alpha 0,858 and declared reliable on all statements. Analysis used test pearson chi-square.The results showed that there was a relationship between peer social support with anxiety in final year students in completing thesis during the pandemic at the University of Riau with p value of 0,022 (< 0,05). Anxiety occurs a lot in students aged 22 years and on average experience very severe anxiety with high support.